The effects of high-quality financial reporting on municipal bond ratings: evidence from US local governments. Issue 5 (3rd September 2021) - Park, Jinsol; Lee, Hakyeon; Butler, J. S.; Denison, Dwight
ABSTRACT: While credit rating agencies mention that a government factor is one criterion for assessing municipal bond ratings, current studies on credit ratings offer relatively little evidence as to how the government factor affects municipal bond ratings, compared to socioeconomic and financial factors. By utilising the award of the Certificate of Achievement for Excellence in Financial Reporting Programme of the Government Finance Officers Association as an indicator for high-quality financial reporting, we find that the quality of financial reporting is one important factor that determines municipal bond ratings. We also demonstrate that the repeated actions of providing high-quality financial reporting are valuable for municipalities by enhancing market credibility and thus improving ratings. The positive impact of high-quality financial reporting is greater for municipalities which have just begun to give a signal of providing transparent financial information to the market than municipalities which have already built market credibility for a long time.